Dignity and Human Rights—Survey Findings on Undergraduate Nursing Students' Conceptualisation and Operationalisation of Dignity - Sheila Douglas; Leah Macaden; Kevin Muirhead; Elaine Webster; Liz Ellis (Nursing Open)
ABSTRACT Aim The aim of the study was to explore how students conceptualise and operationalise dignity with confidence in practice through a human rights lens. Design A quantitative study using an online survey questionnaire. Methods Data were collected using an online survey with 33 questions in three parts: students' conceptualisation of dignity, understanding of human rights and human rights law; students' operationalisation of dignity using a case study designed for this purpose [a fictional character named John]; lastly, students' preferred approaches to dignity education. Results Survey findings revealed students' ambiguity or lack of agreement around dignity being associated with human rights and person‐centred care. There was a sense of students feeling disempowered or lacking confidence in responding to dignity breaches in care, whilst some participants felt equipped to challenge this by most usually referring to clinical staff such as mentors and charge nurses due to the hierarchy in nursing systems within clinical contexts. Conclusion Informed by the findings from this survey, the research team has developed DigniSpace (2024), the first online interactive space for Dignity Education co‐produced with students focusing on the concept of dignity (through a consideration of human rights) that has been designed to help students learn more about the concept and to confidently promote and advocate dignity in practice. This is the first such resource to empower students to interrogate the concept of Dignity using the human rights lens and become change agents to promote and advocate dignity in care as a fundamental human right in any practice context. Implications for Nursing Findings and outputs from this research have used the context of nursing education as a critical opportunity by placing students at the heart of developing DigniSpace (2024) to support the sustainable development of a culture of confidence to provide person‐centred care embedded with dignity. Patient or Public Contributions Findings from this first phase of the study were presented to our project advisory group that included experts with lived experience and their family care partners, who then participated in the co‐design workshops in the second phase of the study to develop DigniSpace—a key output from this project.